The assessment of patients undergoing cardiac surgery for Covid-19: Complications occurring during cardiopulmonary bypass. (May 2022) - Stammers, Alfred H; Mongero, Linda B; Tesdahl, Eric A; Patel, Kirti P; Jacobs, Jeffrey P; Firstenberg, Michael S; Petersen, Courtney; Barletti, Shannon; Gibbs, Autumn
The outbreak of the novel coronavirus pandemic (COVID-19) has resulted in dramatic changes to the conduct of surgery both from a patient management perspective and in protecting healthcare providers. The current study reports on the status of COVID-19 infections in patients presenting for cardiac surgery with cardiopulmonary bypass (CPB) on circuit complications. A tracking process for monitoring the presence of COVID-19 in adult cardiac surgery patients was integrated into a case documentation system across United States hospitals where out-sourced perfusion services were provided. Assessment included infection status, testing technique employed, surgery status and CPB complications. Records from 5612 adult patients who underwent cardiac surgery between November 1, 2020 and January 18, 2021 from 176 hospitals were reviewed. A sub-cohort of coronary artery bypass graft patients (3283) was compared using a mixed effect binary logistic regression analysis. 4297 patients had negative test results (76.6%) while 49 (0.9%) tested positive for COVID-19, and unknown or no results were reported in 693 (12.4%) and 573 (10.2%) respectively. Coagulation complications were reported at 0.2% in the negative test results group versus 4.1% in the positive test result group (p < 0.001). Oxygenator gas exchange complications were 0.2% in the negative test results group versus 2.0% in the positive test results group (p = 0.088). Coronary artery bypass graft patients with a positive test had significantly higher risk for any CPB complication (p = 0.003) [OR 10.38, CI 2.18–49.53] then negative test patients [OR 0.01, CI 0.00–0.20]. The present study has shown that patients undergoing cardiac surgery with CPB who test positive for COVID-19 have higher CPB complication rate than those who test negative.